2020
DOI: 10.1155/2020/8636795
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Periodontal Therapy Recovered the Phagocytic Function of Monocytes in Periodontitis

Abstract: Background. Several studies have focused on the association between periodontitis and systemic implications; however, the biological mechanisms of the immune responses before and after periodontal therapy involved in this relationship, such as phagocytic functions, remain unclear. Objectives. This study aimed to investigate whether periodontal treatment improves the phagocytic function of blood monocytes in patients with severe periodontitis. Materials and Methods. A nonrandomized sample of 55 participants was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Suppressive neutrophils, TLR‐expressing monocyte, immunosenescent cytotoxic T cells, naive, central, and effector memory T cells were affected by periodontal treatment 46,121,123,127 . Further improvement in phagocytic activity, chemotactic response, and ROS production of peripheral blood‐derived cells, including neutrophils and monocytes, was noted 61,62,66,96,131 . Collectively, this suggests a possible causal association between periodontitis and proportion and function of circulating inflammatory cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Suppressive neutrophils, TLR‐expressing monocyte, immunosenescent cytotoxic T cells, naive, central, and effector memory T cells were affected by periodontal treatment 46,121,123,127 . Further improvement in phagocytic activity, chemotactic response, and ROS production of peripheral blood‐derived cells, including neutrophils and monocytes, was noted 61,62,66,96,131 . Collectively, this suggests a possible causal association between periodontitis and proportion and function of circulating inflammatory cells.…”
Section: Discussionmentioning
confidence: 89%
“…Proliferative response of T lymphocytes measured by autologous mixed lymphocyte reaction was increased after successful periodontal treatment 45,128,130 . The treatment also improved the phagocytic activity of both peripheral blood neutrophils and monocytes 66,131 . Circulating neutrophils and monocytes demonstrated increased chemotactic activity following the intervention 96 .…”
Section: Resultsmentioning
confidence: 97%
“…Notwithstanding, Carneiro et al 23 observed a significant reduction of phagocyte functions in individuals with periodontitis. In other studies, authors reported that non-surgical periodontal treatment significantly improved the clinical periodontal status of subjects with periodontal disease and resulted in significantly increased phagocytosis of neutrophils 24 and monocytes 25 to levels observed in control subjects. The elevated number of white blood cells has been associated with the risk of coronary heart disease, cardiovascular disease, atherosclerosis, thrombosis and myocardial ischemia.…”
Section: Discussionmentioning
confidence: 84%
“…Besides, organic acids are produced after sugar metabolism by bacterial plaque and it causes pH reduction and tooth demineralization [ 8 ]. As a result, the periodontal tissues are damaged due to the host immune reaction that arises in response to microbes [ 9 ]. Both the innate and adaptive immune system plays a crucial role in the progression of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that periodontitis enhances the risk of some other diseases such as diabetes, rheumatoid arthritis, obesity, cancer, and cardiovascular diseases, etc. [ 9 , 12 ]. So, it is necessary to take care of this disease.…”
Section: Introductionmentioning
confidence: 99%